Peran Akuntansi Manajemen dalam Meningkatkan Kinerja Keuangan Perusahaan Ritel di Indonesia (International Forum of Researchers and Lecturers, 2024)
Management accounting plays a key role in improving the financial performance of retail companies in Indonesia. By using accurate and relevant financial data, management accounting helps management make effective strategic decisions. In the context of retail companies, management accounting helps in optimizing operational costs, planning budgets, and measuring organizational performance. In this research, we will explore the role of management accounting in improving the financial performance of retail companies in Indonesia.